PENERAPAN WEBSITE DILAN KEPADA MASYARAKAT DI DESA SOBAYAN - Junior, Ryan; Puspitasari, Norma; Pamungkas, Canggih Ajika (Politeknik Indonusa Surakarta, 2024)
Implementing websites in village communities is a strategic step in improving community welfare and participation. By utilizing information technology, websites can provide easy access to information, services and opportunities for village communities. This research presents the background, objectives and impact of implementing websites in villages. Websites in villages can be an effective communication channel between the village government and the community, increasing transparency, participation in decision making, and economic empowerment through the promotion of local products. Apart from that, the website is also a means of education, training and access to health for village communities. Thus, implementing websites in villages not only provides technology, but also allows the community's potential to contribute to development and improve their quality of life. Successful implementation must take into account the specific village context and encourage inclusivity, digital literacy, and the use of technology to achieve sustainable development at the local level. Implementing websites in villages is not only about technology, but also about community empowerment through access to information, participation and economic development. Good implementation must take into account the unique needs of rural communities and ensure that technology can be used effectively to improve their well-beings.